Factors that motivate band members toward band competitions / Mohd. Zahrein Mustaffa - Mustaffa, Mohd. Zahrein (Faculty of Music, 2016)
Marching band is a school's co-curriculum activity that involves playing music using different types and sizes of musical instruments. It involves marching drills and formations, which include military disciplines and techniques with synchronized steps. Annually, marching bands are involved in many events, for example participating and entertaining crowds during schools' sports day, National Day parade, cultural and floral parade and the most intense is band competitions. Currently, most secondary schools in Malaysia have their own marching band that represents the school's pride and joy. The purpose of this study is to examine the factors that motivate secondary school band members in the Klang Valley toward marching band competitions using Walker's seven factors of motivation. This study was narrowed down to only one school in Klang Valley due to difficult procedure to obtain approval from other schools, the school studied is an all-boys school and The subjects for this study are students ranging from form 3 (aged 15) to form 5 (aged 17). A total of forty-eight (N= 48) secondary school band members participated in this study. Subjects were selected from one high school in the Klang Valley. Band members were in form 3, 4 and 5. There were fifteen (n = 15) form 3 students, nineteen (n = 19) form 4 students and fourteen (n= 14) form 5 students. All of the students are male, since the school that was studied was an all-boys school. A questionnaire was prepared for this study which consists 13 items that allow the band members to express the factors that motivate them toward marching band competitions. A 5-point Likert scale was used to record subject's responses